Numerical Investigation Of Dva In Attenuating The Transmitted Handarm Vibration From The Motorboat Engine - Sha’ari, Ahmad Syafiq Nazri (Universiti Sains Malaysia, 2021)
Prolonged exposure to the high level of vibration from motorboat engine handle can lead to the health associated problems such as the Hand-arm Vibration syndromes (HAVs). Therefore, in this study, the attenuation of transmitted hand-arm vibration during operation of motorboat engine is evaluated using simulation approach in MATLAB/Simulink software. One of the Structural Dynamic Modification (SDM) method is applied in this study to attenuate the vibration of motorboat engine handle which is the use of Dynamic Vibration Absorber (DVA). A 2 degree of freedom (2DOF) system that represents the motorboat engine handle with DVA has been modelled and the simulation results are compared to evaluate the vibration attenuation for two cases of engine speeds. The simulation was also caried out for DVA with various mass ratios. The mass ratio designed in this study is based on its effective range, which is 0.05<μ<0.25. From the simulation results, the DVA with mass ratio of μ = 0.25 shows the best performance and successfully reduced the vibration of handle by 98.5 % and 99.8 % for both engine speeds 1 and 2, respectively. Then, a SDOF model which based on Reynolds and Soedel, (1972) models is coupled with the motorboat handle model to investigate the effectiveness of the DVA in reducing the transmitted hand-arm vibration. The result shows that the hand-arm vibration is reduced by 88.6 % and 95.3 % for both engine speeds 1 and 2, respectively. As a conclusion, this study proved that DVA can be one of an effective way to reduce hand-arm vibration for motorboat engine handle.